Contribution of common chronic conditions to midlife physical function decline: The Study of Women's Health Across the Nation - Brittney S. Lange-Maia; Kelly Karavolos; Elizabeth F. Avery; Elsa S. Strotmeyer; Carrie A. Karvonen-Gutierrez; Bradley M. Appelhans; Imke Janssen; Sheila A. Dugan; Howard M. Kravitz (BMC, 2020)
Abstract Background Chronic conditions are associated with worse physical function and commonly develop during midlife. We tested whether the presence of 8 chronic conditions, or the development of these conditions, is associated with declines in physical function among midlife women as they transition into early late life. Methods Participants (N = 2283) were from the Study of Women's Health Across the Nation. Physical function was assessed at 8 visits starting at the study's fourth clinic visit in 2000/2001 through follow-up visit 15 (2015/2017) using the Short Form-36 Physical Function subscale. Chronic conditions included diabetes, hypertension, osteoarthritis, osteoporosis, stroke, heart disease, cancer, and depressive symptoms. Repeated-measures Poisson regression modeled associations between 1) prevalent chronic conditions at analytic baseline (visit 4) and longitudinal physical function, and 2) change in physical function associated with developing a new condition. Models were adjusted with the total number of other chronic conditions at visit 4. Results In separate fully-adjusted longitudinal models, prevalent heart disease and osteoporosis were associated with 18% (IRR = 0.815, 95% confidence interval [CI]: 0.755-0.876) and 12% (IRR = 0.876, 95% CI: 0.825-0.927) worse initial physical function, respectively. Prevalent osteoarthritis was associated with approximately 6% (IRR = 0.936, 95% CI: 0.913-0.958) worse initial physical function, and a slight additional worsening over time (IRR = 0.995, 95% CI: 0.994-0.996). A 12% (IRR = 0.878, 95% CI: 0.813-0.950) decrease in physical function concurrent with stroke development was evident, as was accelerated decline in physical function concurrent with heart disease development (IRR = 0.991, 95% CI: 0.988-0.995). Conclusions Initial prevalent conditions related to the musculoskeletal system were associated with worse initial physical function, with some evidence of accelerated decline in physical function with osteoarthritis. Stroke and heart disease are less common than osteoarthritis in this age group, but the severe effects of these conditions on physical function shows the need for a greater focus on cardiovascular health during midlife. Women who develop chronic conditions during midlife may be at particular risk for poor physical function as they age, warranting disability prevention efforts focused on this population.